Analisis Gerak Tari Campak di Sanggar Pelandok Laki Kecamatan Tanjung Pandan, Kabupaten Belitung - Apriani, Reni; Darmawati, Darmawati (Darul Yasin Al Sys, 2023)
This study aims to analyze the motion of measles dance in pelandok laki studio, Tanjung Pandan sub-district, Belitung Regency. This research uses qualitative research with descriptive methods. The object of this research is Measles Dance in Sanggar Pelandok Laki, Tanjung Pandan District, Belitung Regency. The main instrument of this research is the researcher himself. Based on the results of the study it can be concluded that Measles dance seen from the aspects of space, time and energy aspects of Measles dance has several elements contained in Measles dance movements. Measles dance observed from the perspective of the element of motion space is 6 straight lines. So the dominant in the motion of Measles Dance is a straight motion that has the impression of calm and balanced with full of enthusiasm. The volume in the measles dance is 6 medium volumes, so the dominant volume is medium volume, which means it describes the joy or cheerfulness of teenagers in entertaining the community after the rice harvest. The dominant level is the medium level. The direction of facing in the measles dance is 4 facing the front 2 facing the right side left which describes intimacy. While the focus of view in Measles Dance movements is dominant to the hand or shawl.